Nilai Waktu Uang dan Legitimasi Syariah: Analisis Konsep Time Value of Money dan Economic Value of Time Dalam Keuangan Islam - Sirojul Munawwar; Imanda Firmantyas Putri Pertiwi (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The Time Value of Money (TVM) serves as a core principle in conventional finance, asserting that current money is worth more than future money due to inflation, risk, and investment opportunities. However, Islamic finance debates this concept due to its strong association with interest-based practices, which fall under the prohibition of riba (usury). This study analyzes the concept of TVM in conventional economics, examines the Islamic financial perspective on the value of money over time, compares TVM with the Economic Value of Time (EVT), and evaluates its legitimacy based on Sharia principles and maqashid al-shariah. Using a qualitative-descriptive library research method, this study analyzes various recent scientific literatures. The results indicate that Islamic economics does not reject the value of time absolutely. Instead, it rejects any automated increase in monetary value that arises solely from the passage of time without real economic activity. As an alternative, Islamic economics offers the EVT concept, which treats time as a productive factor to generate economic value through genuine business operations. Islamic finance implements this time value through real transaction-based contracts including murabahah, ijarah, and mudharabah. These applications possess valid Sharia legitimacy as long as they remain free from riba (usury), gharar (uncertainty), and maisir (gambling) while promoting public welfare under maqashid al-shariah. This paradigm shift provides a strategic opportunity for the Islamic financial industry to build a more inclusive, equitable, and sustainable economic system.